2012
DOI: 10.1590/s0100-879x2012007500074
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical effect of a pequi oil-rich diet on the development of atherosclerosis: balance between antioxidant and hyperlipidemic properties

Abstract: Pequi is the fruit of Caryocar brasiliense and its oil has a high concentration of monounsaturated and saturated fatty acids, which are anti- and pro-atherogenic agents, respectively, and of carotenoids, which give it antioxidant properties. Our objective was to study the effect of the intake of a cholesterol-rich diet supplemented with pequi oil, compared to the same diet containing soybean oil, on atherosclerosis development, and oxidative stress in atherosclerosis-susceptible LDL receptor-deficient mice (LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 33 publications
1
38
0
5
Order By: Relevance
“…provides nutritional value, since oleic acid consumption is related to a decrease in low density lipoprotein (LDL) and the maintenance of HDL cholesterol (high-density lipoprotein) levels in humans and animals and, consequently, a reduction in coronary disease risk (Ramadan et al, 2012;Katan et al, 1994). However, palmitic acid, a SFA, is also found in large amounts in Caryocar spp., whose pro-atherogenic and cytotoxic effects are well known (Moreno et al, 2016;Aguilar et al, 2012). Because of this, the challenge of researchers is to evaluate whether the proportion of the cardiovascular protection compounds present in pequi is adequate to neutralize the effects of SFA on blood lipids.…”
Section: Effects On Lipid Profile and Cardiovascular Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…provides nutritional value, since oleic acid consumption is related to a decrease in low density lipoprotein (LDL) and the maintenance of HDL cholesterol (high-density lipoprotein) levels in humans and animals and, consequently, a reduction in coronary disease risk (Ramadan et al, 2012;Katan et al, 1994). However, palmitic acid, a SFA, is also found in large amounts in Caryocar spp., whose pro-atherogenic and cytotoxic effects are well known (Moreno et al, 2016;Aguilar et al, 2012). Because of this, the challenge of researchers is to evaluate whether the proportion of the cardiovascular protection compounds present in pequi is adequate to neutralize the effects of SFA on blood lipids.…”
Section: Effects On Lipid Profile and Cardiovascular Diseasesmentioning
confidence: 99%
“…Other in vivo studies carried out in human athletes (runners) detected a general tendency for total cholesterol (TC) and LDL to decrease over age, mainly for men, after C. brasiliense pulp oil intake (MirandaVilela et al, 2009a). Aguilar et al (2012) found that risk factors for atherosclerosis, such as oxidized LDL (oxLDL), oxidative stress, and macrophage liberation of free radicals, were reduced in mice receiving a cholesterol-rich diet supplemented with 7% C. brasiliense (undefined) oil, suggesting that pequi oil confers an important antioxidant effect, thereby reducing oxidative stress, including oxLDL antibodies. Moreover, pequi oil reduced atherosclerotic lesions in the aorta, which is a more relevant atherosclerotic site for humans than the aortic valve.…”
Section: Effects On Lipid Profile and Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Também foi descrita a ação neuroprotetora do extrato etanólico da casca de pequi em cérebro de ratos submetidos à isquemia e reperfusão (Miguel et al 2012). Aguilar et al (2012) avaliaram a ação do óleo do pequi na aterogêne-se e concluíram que o pequi retarda esse processo nas fases iniciais, possivelmente devido à sua atividade antioxidante. No entanto, o aumento do colesterol no soro induz a maior migração de LDL para a íntima de artérias, acelerando a formação de lesões ateroscleróticas avançadas.…”
Section: Introductionunclassified
“…Caryocar Brasiliense Camb. (Caryocaraceae) is a tree distributed in the Cerrado region that produces pequi, appreciated for its sensory characteristics: color, flavor and aroma and for its nutritional characteristics: high contents of fiber, lipids and total energy (Aguilar et al, 2012;Cardoso et al, 2013). It is reported by Rodrigues et al (2011) that pequi fruits showed durability nine to twelve days during storage.…”
Section: Introductionmentioning
confidence: 99%